Child-free Lifestyle in Muslim Societies: A Review of Islamic Law and Indonesian Kiai Figures Perspective - Muhammad Miftah Alkausar; Ita Rahmania Kusumawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The decision of a husband and wife not to have children caused a polemic in Indonesian society because it was suspected that it violated the prevailing norms, cultural values and religious teachings. At the same time, this trend began to develop in Indonesia after the recognition of several public figures who decided to be child-free. This study aimed to find out how the process of the spread of a child-free culture and prevention of pregnancy that occurs in the community and how the provisions of Islamic law and policies as well as counter the kiai leaders of the Tebuireng Islamic Boarding School in responding to the child-free phenomenon. The type of this research is descriptive field research using a phenomenological approach. Primary data sources were obtained through interviews and documentation of child-free actors and kiai figures from the Tebuireng Islamic Boarding School and supported by secondary data in the form of written literature or scientific works. The results of this study explain that child-free couples or individuals have various motives and methods of preventing pregnancy. Kiai leaders of the Tebuireng Islamic Boarding School and the provisions of Islamic law are of the view that the law of a child-free lifestyle is makrūh and cannot benefit from marriage ‘tark al-afdal’ because it is considered contrary to maqāşid al-syarī’ah ‘the purpose of sharia’, maqāşid al-nikāḥ ‘purpose of marriage’, and the fiṭrah or nature offspring.